2000
DOI: 10.1111/0031-868x.00152
|View full text |Cite
|
Sign up to set email alerts
|

Application of Digital Photogrammetry to Complex Topography for Geomorphological Research

Abstract: This paper is concerned with the application of automated digital photogrammetry, using 1:3000 scale photography, to complex, natural landform surfaces, of typical interest to geomorphologists. It assesses the quality of the results obtained using a relatively cheap and readily available area based stereomatching package, in terms of precision, accuracy and external reliability. Precision is investigated with reference to the confidence that can be placed in individual matches. Accuracy is evaluated using spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
152
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 179 publications
(163 citation statements)
references
References 20 publications
4
152
0
1
Order By: Relevance
“…The mean error (ME) indicates the presence of bias or systematic errors; whereas the standard deviation of error (SDE) provides a measure of surface variability or precision. Past research (Li, 1988;Lane et al, 2000;Chandler et al, 2005) has demonstrated that these two statistics are more informative for surface comparison than the RMSE more traditionally used in surveying. Primary data output for the esker study yielded aerial photography, derivative DEMs and orthophotographs from stereo-pairs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean error (ME) indicates the presence of bias or systematic errors; whereas the standard deviation of error (SDE) provides a measure of surface variability or precision. Past research (Li, 1988;Lane et al, 2000;Chandler et al, 2005) has demonstrated that these two statistics are more informative for surface comparison than the RMSE more traditionally used in surveying. Primary data output for the esker study yielded aerial photography, derivative DEMs and orthophotographs from stereo-pairs.…”
Section: Resultsmentioning
confidence: 99%
“…However, a lower coefficient increases the chance of 'false matches' and potential inclusion of erroneous data points. This effect is well known (Gooch et al, 1999;Lane et al, 2000) and some judgment is required in selecting the optimum correlation coefficient. It is comforting that a range of coefficients (0·7-0·8) appear to have produced a surface which is of an acceptable accuracy, despite some variation in point density.…”
Section: Earth Surface Processes and Landformsmentioning
confidence: 99%
“…The identification and classification of landforms from remote sensing data is increasingly popular among scientists [5,[9][10][11]. Tasks are carried out at various levels of scale, from global-scale landform classification [12] to a local-scale delineation of landforms [13,14].…”
Section: Landform Characterizationmentioning
confidence: 99%
“…In the floodplain areas, the movement of water is hardly detected using a DEM as it is controlled by very small topographic features, specifically if the mesh size is not fine enough to represent these small features such as narrow channels connecting main rivers and floodplains (Yamazaki et al 2012, Saksena andMerwade 2015). Moreover, the presence of noise and canopy in the DEM highly affect the drainage network in these regions, specifically with small mesh sizes (Lane, James andCrowell 2000, Polidori andSimonetto 2014).…”
Section: Discussionmentioning
confidence: 99%